Fraud Prevention Portrait in Sharia Financial Institutions: It Takes a Village - Faisol Faisol; Mohammad Nizarul Alim; Siti Munawaroh (JAFFA, 2023)
Fraud prevention is very necessary to be applied in Islamic financial institutions, especially in BMT NU, it aims to keep the organization's assets from human hands crime that can harm institutions BMT NU. The purpose of this study was to describe the fraud prevention model in BMT NU Torjun branch. This study uses a case study approach to investigate the fraud prevention model in BMT NU Torjun branch by interviewing several informants who are working in the world of work BMT NU Torjun branch. The findings of this study can be concluded that the fraud prevention model in BMT NU Torjun branch starts from BMT NU managers who must run according to the SOP (standard operating procedures) that have been established in the BMT NU Torjun branch. To prevent fraud in BMT NU Torjun branch, an internal audit is conducted by the central RKM team which is carried out every month twice on the second weekend, so that one's space is getting narrower to commit fraud in BMT NU. Furthermore, the fraud prevention model at BMT NU Torjun branch has strict supervision from several parties, both supervision from area managers, DPS (Sharia Supervisory Board), and supervision from the headquarters. With the Prevention of fraud set in the BMT NU Torjun branch will effectively minimize the occurrence of fraud, even avoid fraud actions that can harm the institution BMT NU Torjun branch.